Sex work among female workers in the traditional mining sector in Mali – results from the ANRS-12339 Sanu Gundo cross-sectional study in 2015. Issue 3 (27th September 2019) - Kounta, Cheick Haïballa; Sagaon-Teyssier, Luis; Balique, Hubert; Diallo, Fodié; Kalampalikis, Nikos; Mora, Marion; Bourrelly, Michel; Suzan-Monti, Marie; Spire, Bruno; Keita, Bintou Dembélé
Abstract : Female sex workers (FSW) in mining sites are considered to be at very high risk of HIV infection. We aimed to characterize FSW at the Kôkôyô artisanal gold mining site in Mali, and identify factors associated with sex work using data from ANRS-12339 Sanu Gundo, a cross-sectional survey conducted in 2015 at the mine by ARCAD-SIDA, a Malian non-governmental organisation. People attending HIV-prevention activities were invited to participate in the quantitative and qualitative parts of the survey. A probit logistic regression was used for data analysis. Of 101 women who participated in the survey, 26.7% reported sex work as their main activity. Multivariate analysis showed that the probability of sex work as a main activity decreased by 1% per 1-year age increase ( p = 0.020). Sex work was significantly more likely to be reported by single, divorced and widowed women (25.4% probability; p = 0.007). FSW were significantly more likely to be non-Malian (36.3% probability; p = 0.003), more likely to have a secondary activity (77% probability; p = 0.002), to work fewer than 56h/week (40.2% probability; p = 0.001) and to be in good health (12.1% probability; p = 0.016). In addition, being aware of the existence of sexually transmitted infection, using psychoactive substances, and having unprotected receptive anal sex during the previous six months were significantly associated with sex work (50.2%; p = 0.006; 45.6%, p = 0.003; and 7.4%, p = 0.016 probability, respectively). Qualitative findings confirm that poverty and boyfriends' refusal to use condoms remain key barriers to systematic condom use among FSW.